Analysis of Indonesian state policy in resolving medical disputes with a restorative justice approach - Widjayanto, Indra (ARKA INSTITUTE, 2025)
Medical disputes that are resolved through litigation often have negative impacts, such as the criminalization of medical personnel, waste of time and money, and the non-fulfillment of a sense of substantive justice for victims. In this context, the restorative justice approach has emerged as an alternative dispute resolution that is more humanist, oriented towards recovery and reconciliation. This study aims to analyze in depth the potential and urgency of applying the restorative justice approach in medical dispute resolution in Indonesia, as well as evaluate the legal, ethical and institutional obstacles faced. The method used is normative legal research with a conceptual approach and statute approach. The results of the study show that restorative justice can be a fairer, faster, and more efficient solution in resolving medical disputes if supported by appropriate regulations, professional mediation institutions, and active involvement of professional organizations and law enforcement officials. Therefore, policy reform is needed through the establishment of specific rules on RJ in medical disputes, the provision of mediator resources who understand medical ethics, and strengthening legal protection mechanisms for all parties. Thus, restorative justice in medical disputes is expected to be able to create a more humanist, responsive, and socially just health law system in Indonesia.